ANALISIS SISTEM INFORMASI ASTRA BERBASIS WEB TERHADAP KEPUASAN PELANGGAN - sasa ani arnomo (Universitas Putera Batam, 2013)
Website as electronic information media may present a variety of information quickly, effectively and efficiently. Optimal utilization of information technology is one of the key components in providing customer satisfaction. From these statements it is doing research analysis astra web-based information systems to customer satisfaction with dseskriptif quantitative research methods. Astra web-based information systems as variables x (independent) and customer satisfaction as the y variable (dependent). And produce research that the quality of web-based information system astra views of Usability, Graphic Design, Contents, Compatibility, Loading Time, accessibility, Interactivity is quite good and beneficial to the customer. In terms of customer satisfaction, the customer satisfied with the quality of the product / service, price, service quality, and ease to get astra product. While the trial found that the effect of quality web-based information systems astra affects customer satisfaction.